Case Report: ABO-incompatible living donor liver transplantation in a patient with associated Rosai–Dorfman–Destombes disease, first reported case - Sahoo, Bhabani Sankar; Makki, Kausar; Saini, Vikas; Srivastava, Piyush; Vij, Vivek (Frontiers in Transplantation, 2025)
Rosai–Dorfman–Destombes disease (RDD), a rare histiocytic proliferation, is often associated with lymphadenopathy and extranodal manifestations, including involvement of the liver. We report a unique case of RDD presenting with chronic liver disease (CLD) in a 7-year-old boy, highlighting the association between these conditions. The patient underwent ABO-incompatible living donor liver transplantation (LDLT), a procedure not previously documented in the context of RDD. Successful transplantation was preceded by a desensitization protocol including rituximab and immunoadsorption, and was followed by a satisfactory postoperative course. This case underscores the need for further investigation into the relationship between RDD and CLD and the potential of LDLT as a life-saving treatment option in such complex cases.